Tradition and Transformation: Islamic influence on animal slaughter in Padang Bolak funeral customs - Siregar, Ilham Ramadan; Rababah, Mahmoud Ali; Amiruddin, Amiruddin; Akhyar, Akhyar; Hasibuan, Sri Wahyuni (UIN Maulana Malik Ibrahim Malang, 2024)
This research aims to describe the acculturation of Islam and local culture in the tradition of animal slaughter at funeral ceremonies preserved by the Padang Bolak community, as part of the religious system reflecting the community's understanding of the Hadith. This study is a field study employing a qualitative method within the framework of living Hadith theory. The research findings indicate that this tradition of animal slaughter at funeral ceremonies in the community is motivated by several factors, including efforts to preserve customs and culture, as an act of devotion to parents, the deceased's will to conduct an animal slaughter before passing away, to honor guests, maintain the good name of the deceased parents within the community, as an expression of love for parents, and the belief that the merits of charity performed on that day will benefit the deceased. In Islamic legal studies, this tradition is fundamentally contradictory to Islamic teachings in all its processes and requirements. The acculturation of Islam with this tradition has led to modifications that eliminate elements conflicting with Islamic teachings. Further studies are needed on how such modifications can aid in understanding and potentially guiding the process of cultural adaptation in other Islamic communities. Penelitian ini bertujuan untuk menggambarkan akulturasi Islam dan budaya lokal dalam tradisi penyembelihan hewan pada upacara pemakaman yang dipertahankan oleh komunitas Padang Bolak, sebagai bagian dari sistem religius yang mencerminkan pemahaman masyarakat tentang Hadits. Studi ini adalah studi lapangan yang menggunakan metode kualitatif dalam kerangka teori Hadits hidup. Temuan penelitian menunjukkan bahwa tradisi penyembelihan hewan pada upacara pemakaman di komunitas tersebut didorong oleh beberapa faktor, termasuk upaya untuk melestarikan adat dan budaya, sebagai tindakan pengabdian kepada orang tua, keinginan almarhum untuk melakukan penyembelihan hewan sebelum meninggal, untuk menghormati tamu, mempertahankan nama baik orang tua yang telah meninggal di dalam komunitas, sebagai ungkapan cinta kepada orang tua, dan keyakinan bahwa pahala amal yang dilakukan pada hari itu akan menguntungkan almarhum. Dalam studi hukum Islam, tradisi ini secara mendasar bertentangan dengan ajaran Islam dalam semua proses dan persyaratannya. Akulturasi Islam dengan tradisi ini telah mengarah pada modifikasi yang menghilangkan elemen-elemen yang bertentangan dengan ajaran Islam. Studi lebih lanjut diperlukan tentang bagaimana modifikasi tersebut dapat membantu dalam memahami dan berpotensi mengarahkan proses adaptasi budaya di komunitas Islam lainnya.